Corporate citizenship and family business - Seaman, Claire (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Current models of corporate citizenship largely consider business as one coherent entity. This view of business as a corporate force overlooks the growing evidence that most businesses are run by families. Family businesses are the most common form of business in existence - across countries, continents and geopolitical divides - and yet we know remarkably little about their approach to corporate citizenship. Where families run businesses, they create a concentration of family values that - for good or ill - influence the way business practices and behaviours develop. The role of the family in business has, therefore, an influence on the development of society that is partially mediated through corporate citizenship. This book pulls together current thinking from several diverse research fields that intersect with family business research to offer insight into current research and examples of practice for those studying and researching in the fields of family business, business values and corporate practice. The book will also explore the fact that family businesses tend to take a longer-term approach to business and that this is reflected in their behaviour towards the environment, community engagement, employee development and innovation. Bringing together contributions from researchers in the diverse fields of family business, philanthropy, community engagement, corporate social responsibility, innovation and policy, this book explores the many ways in which family businesses contribute to the corporate citizenship agenda"--
OCLC-licensed vendor bibliographic record.
Keywords: Family-owned business enterprises; Social responsibility of business; Corporate governance; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business